Exceptional learners : introduction to special education - Hallahan, Daniel P., 1944- (Allyn and Bacon, 2000)
Exceptionality and special education. Current trends and issues. Multicultural and bilingual aspects of special education. Mental retardation. Learning disabilities. Attention deficit hyperactivity disorder. Emotional or behavioral disorders. Communication disorders...